Air-conditioning supports for buildings: Challenges for a sustainable city - Silva, Wildson Wellington; Soares, Willames de Albuquerque; Monteiro, Eliana Cristina Barreto (Revista Nacional de Gerenciamento de Cidades, 2023)
With the advancement of technology and the increase in global temperatures, there has been a demand for individual and collective cooling systems in residential and commercial buildings, leaving air conditioning equipment and their respective supports exposed on their facades. The objective of this study is to evaluate the degradation of reinforced concrete supports in a case study. It was found that 49.5% of the buildings have supports for air conditioners in the external area of their facades and of these 69% are reinforced concrete. From the aerial images it was possible to observe cracks in 90% of the supports and 21% presented partial collapse of the structure. It is concluded that the failure in the design of the reinforced concrete support without giving importance to the minimum requirements of coverage and quality control in the manufacture of concrete, are decisive in the increase of porosity and the entry of aggressive agents. The low useful life of these supports is associated with the risk of serious or fatal accidents with the fall of parts of these structures and leads to frequent replacement, demanding more cement consumption and more construction waste.